GERAKAN POPULISME ISLAM DAN DEMOKRASI INDONESIA: REFLEKSI DARI PILPRES 2019 - Saepudin (Universitas Djuanda Bogor, 2024)
This research reveals that the reflection of the 2019 presidential election, the Islamic populism movement, which is only considered a threat (destructive) to Indonesian democracy, is an inappropriate view; Islamic populism must also be seen as a constructive political movement, as a form of demand for justice and welfare of the majority population. This attitude is part of the control of the democratic system, which is based on considerations of sociological and historical aspects that the majority of the Indonesian population adheres to Islam. Responding to Islamic populism in Indonesia must be done by fully understanding the meaning of democracy and the values ​​in Pancasila and Bhinneka Tunggal Ika. Because ideally every political movement that provides a critical attitude must be interpreted as part of democratic dynamics.